2022
DOI: 10.3389/fpubh.2022.1020937
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on palliative care practice: A survey of clinical oncologists

Abstract: BackgroundPalliative care is an essential intervention to improve the quality of life for patients with cancer, whereas the ongoing COVID-19 pandemic poses a challenge to supportive and palliative care providers. This survey aims to explore the current status of palliative care practice for cancer and the influence of COVID-19, from the perspective of oncologists.MethodsThe semi-structure electronic questionnaire was designed. Mixed-mode surveys including electronic questionnaires, face-to-face interactions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Thyroid function tests, urinalysis, coagulation parameters, etc., are also regularly measured during treatment at the times in the assessment schedules and as clinically indicated. Due to the impact of the COVID-19 pandemic ( 26 ), the periodic review during the consolidation therapy phase allows for a slight delay, but not exceeds one week. Serious AEs (SAEs) occurring during treatment or until the last dose of consolidation toripalimab, should be recorded and reported immediately and not exceeding 24h after the knowledge of SAEs.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Thyroid function tests, urinalysis, coagulation parameters, etc., are also regularly measured during treatment at the times in the assessment schedules and as clinically indicated. Due to the impact of the COVID-19 pandemic ( 26 ), the periodic review during the consolidation therapy phase allows for a slight delay, but not exceeds one week. Serious AEs (SAEs) occurring during treatment or until the last dose of consolidation toripalimab, should be recorded and reported immediately and not exceeding 24h after the knowledge of SAEs.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Nevertheless, other studies suggested different RT doses and segmentations played various immunomodulatory role ( 87 ). Some scholars considered low-dose RT, which is commonly used for patients with metastatic diseases as palliative care ( 91 , 92 ), can better induce anti-tumor immune activation at the molecular level, reshape TIME, and improve the infiltration and function of effector immune cells in distant tumor foci ( 9 , 93 95 ). Therefore, anti-tumor responses outside the radiation field strengthened by low-dose RT were termed the “RadScopal effect” by them ( 9 , 96 ).…”
Section: Abscopal Effect Of Radiation Combined With Immunotherapymentioning
confidence: 99%